Reviving A Distinctive Medical Ethic - Churchill, Larry R. (The Hastings Center report, 1989)
Our culture is well on its way to reducing medical ethics to legal requirements, general citizen ethics, or personal values. A distinctive ethic for medicine provides critical distance and moral meaning for the profession and an enriched societal ethic.